Symposium 4: Repositories for Teaching Materials and Learning Objects enablers and Barriers to Use: Symposium Introduction - Morón-García, Sue (Proceedings of the International Conference on Networked Learning, 2006)
This symposium aims to explore the issues around the use of repositories for teaching materials and learning objects. The focus is on enablers and barriers to the use of repositories. Margaryan et al focus on the social aspects of sharing and reuse, considering the relationships between repositories and communities, and using an Activity Theory perspective to analyse the learning object repositories and their communities as sociocultural activity systems. Smith provides an example of a growing community of practitioners who are developing resources out of a shared need, highlighting the rules of engagement that users and contributors have to follow. Morón-García describes a short piece of research exploring the attitudes of teachers in further and higher education to sharing digital teaching and learning materials. The aim of this research was to explore the barriers and enablers to the creation of a regional and institutional repository services.